Meretas Jalan Menuju Kesetaraan: Studi Pemberdayaan Penyandang Disabilitas Mental di Sentra Margo Laras, Pati - Naziihah, Dzikrina Salsabil; Hamidah, Kamilia (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2023)
Mental health is a condition in which an individual can develop physically, psychologically, spiritually, and socially such that the individual recognises his own strengths, can overcome pressure, work productively, and contribute to his community. According to 2018 Basic Health Research (Riskesdas) data, more than 19 million people over the age of 15 experience emotional mental disorders, and more than 12 million people over the age of 15 experience depression, implying that efforts to treat people with mental disabilities require extensive rehabilitation efforts. This is a qualitative descriptive field study research on the practise of rehabilitation and empowerment of individuals with mental disabilities conducted at the Margo Laras Centre in Pati. Supporting data was gathered by direct observation at the Margo Laras Centre, direct interviews with terminated Beneficiaries and the rehabilitation team at the Margo Laras Centre, Pati, and documentation.This study found that rehabilitation and empowerment initiatives for people with mental disabilities lead to recipients' independence, particularly in the areas of social functioning, good communication, and economic independence.